Kölcsönzés, átszabás, reklamáció: Adalékok az újrajátszás kortárs popzenei változataihoz - Fodor, Péter; Lengyel, Zsanett; Urbán, Andrea (Studia Litteraria, 2024)
As there have been major shifts in the field of modern pop music when it comes to multimedia presence, platform types, functions, and consumption, the content and form of music videos have changed consequently. Postmodern ideas, such as the recognition that everything has already been attained, appeared in 80s and 90s productions and impacted the blossoming age of music videos after the millennium. is study explores major directions artists have taken visually from different techniques of citations (Madonna), through creating a patchwork of preceding trends and figures (Lady Gaga) as well as mimicking and altering culturally ingrained images (Lana Del Rey), to individually constructed, interreferential and reflective self-mythology (Taylor Swi). Through the interpretation of music videos and short clips, we aim to highlight various mechanisms of re-enactment, how techniques such as cutting, transferring, de- and recontextualizing certain details formulate meaning, and how methods varied throughout the years. When visual extensions of sound and lyrics are understood as a continuation or extraversion of tradition, artworks are inevitably linked to the past, whereas the usage of reenactment variants within one’s lifework vitalizes itself. With the rise of TikTok, revisiting and reclaiming the past, inviting memories as building blocks of self-mythology exceeds the level of the artist saliently, as the artwork is tailored by an audience; influence works as a pendulum.